2013
DOI: 10.1186/1479-5876-11-284
|View full text |Cite
|
Sign up to set email alerts
|

Novel compound heterozygous mutations in the MYO15A gene in autosomal recessive hearing loss identified by whole-exome sequencing

Abstract: BackgroundInherited genetic defects play an important role in congenital hearing loss, contributing to about 60% of deafness occurring in infants. Hereditary nonsyndromic hearing loss is highly heterogeneous, and most patients with a presumed genetic etiology lack a specific molecular diagnosis.MethodsBy whole exome sequencing, we identified responsible gene of family 4794 with autosomal recessively nonsyndromic hearing loss (ARNSHL). We also used DNA from 56 Chinese familial patients with ARNSHL (autosomal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Studies of the MYO15A mutation in humans have usually been performed in the Middle East, where consanguineous families are more common ( Bashir et al, 2012 ; Belguith et al, 2009 ; Brownstein et al, 2011 ; Cengiz et al, 2010 ; Diaz-Horta et al, 2012 ; Duman et al, 2011 ; Fattahi et al, 2012 ; Kalay et al, 2007 ; Liburd et al, 2001 ; Nal et al, 2007 ; Shearer et al, 2009 ). However, as next-generation sequencing methods have become more popular, MYO15A mutations have been reported from various parts of the world, and the importance of the MYO15A mutation has emerged ( Besnard et al, 2014 ; Gao et al, 2013 ; Woo et al, 2013 ; Yang et al, 2013 ). The frequency of the MYO15A mutation was first reported by Friedman et al (1995) , who reported that 2% of the residents of Bengkala, Bali, had nonsyndromic autosomal recessive deafness due to the MYO15A mutation ( Friedman et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the MYO15A mutation in humans have usually been performed in the Middle East, where consanguineous families are more common ( Bashir et al, 2012 ; Belguith et al, 2009 ; Brownstein et al, 2011 ; Cengiz et al, 2010 ; Diaz-Horta et al, 2012 ; Duman et al, 2011 ; Fattahi et al, 2012 ; Kalay et al, 2007 ; Liburd et al, 2001 ; Nal et al, 2007 ; Shearer et al, 2009 ). However, as next-generation sequencing methods have become more popular, MYO15A mutations have been reported from various parts of the world, and the importance of the MYO15A mutation has emerged ( Besnard et al, 2014 ; Gao et al, 2013 ; Woo et al, 2013 ; Yang et al, 2013 ). The frequency of the MYO15A mutation was first reported by Friedman et al (1995) , who reported that 2% of the residents of Bengkala, Bali, had nonsyndromic autosomal recessive deafness due to the MYO15A mutation ( Friedman et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of mutations in MYO15A on hearing have been investigated extensively. MYO15A mutations have been regarded as leading to congenital severe to profound hearing loss ( Belguith et al, 2009 ; Brownstein et al, 2011 ; Gao et al, 2013 ; Kalay et al, 2007 ; Liburd et al, 2001 ; Shearer et al, 2009 ; Wang et al, 1998 ). In contrast, it was also reported that a mutation in exon 2 of MYO15A resulted in some residual hearing ( Bashir et al, 2012 ; Cengiz et al, 2010 ; Nal et al, 2007 ), especially at low frequencies, suggesting that there may be a genotype-phenotype correlation.…”
Section: Introductionmentioning
confidence: 99%
“…[Ammar‐Khodja et al., ], [Atik et al., ], [Bademci et al., ],[Bashir et al., ], [Belguith et al., ], [Brownstein et al., ], [Brownstein et al., ], [Cengiz et al., ], [Chang et al., ], [Chen et al., ], [Diaz‐Horta et al., ], [Duman et al., ], [Fattahi et al., ], [Gao et al., ], [Gu et al., ], [Imtiaz et al., ], [Kalay et al., ], [Lezirovitz et al., ], [Li et al., ], [Liburd et al., ], [Miyagawa et al., ; Miyagawa et al., ], [Miyagawa et al., ], [Moteki et al., ], [Nal et al., ], [Neveling et al., ], [Park et al., ], [Rehman et al., ], [Riahi et al., ], [Schrauwen et al., ], [Shafique et al., ], [Shahin et al., ], [Shearer et al., ], [Sloan‐Heggen et al., ], [Sloan‐Heggen et al., ], [Vona et al., ], [Vozzi et al., ], [Wang et al., ], [Woo et al., ], [Xia et al., ], [Yano et al., ], [Yang et al., ]…”
Section: Articles Cited In the Online Supporting Informationmentioning
confidence: 99%
“…However, this approach is highly expensive and time consuming for identifying pathogenic variants when there are hundreds of genes in a candidate region. Whole‐exome sequencing (WES) can be used to identify causative genes and mutations of heritable disease with high efficiency and accuracy . WES allows parallel sequencing of billions of nucleotides at a low cost and high speed, and, in recent years, it has become a powerful tool to identify novel genes and mutations associated with hereditary hearing loss …”
Section: Introductionmentioning
confidence: 99%
“…Whole-exome sequencing (WES) can be used to identify causative genes and mutations of heritable disease with high efficiency and accuracy. 6 WES allows parallel sequencing of billions of nucleotides at a low cost and high speed, and, in recent years, it has become a powerful tool to identify novel genes and mutations associated with hereditary hearing loss. 1 Zebrafish (Danio rerio) is an excellent animal model used to study inner ear dysfunction because of strong genetics, excellent embryology, and in vivo visualisation potential.…”
mentioning
confidence: 99%